Attitude tracking control for reentry vehicles using centralised robust model predictive control - Chai, Runqi; Tsourdos, Antonios; Gao, Huijun; Chai, Senchun; Xia, Yuanqing (Elsevier, 2022)
In this work, a centralised robust model predictive control (CRMPC) algorithm is proposed for reentry vehicles to track reference attitude trajectories subject to state/input constraints and uncertainties. In contrast to most designs that apply a cascade control structure for the two-timescale attitude dynamical systems, the proposed control scheme utilises a centralised structure to avoid additional controller development and parameter turning. By designing a nonlinear feedback law and tightening the system constraints, robust constraint satisfaction can be ensured for all admissible uncertainties. In addition, to guarantee the recursive feasibility and closed-loop stability of the proposed CRMPC, a terminal controller, along with a terminal region, is introduced. The validity of using the proposed approach to solve the considered problem is confirmed by executing several experimental studies, which were compared against two other established methods.
Keywords: Robust model predictive control; Reentry vehicle; Attitude tracking; Nonlinear feedback law